Limited Incisional Drainage and Negative-Pressure Wound Therapy in an Acute Morel-Lavallée Lesion - Eui-Sung Choi; Jae-Young Yang; Byung-Hyun Ahn (Journal of Trauma and Injury)
A Morel-Lavallée lesion is a post-traumatic closed degloving soft tissue injury after blunt trauma. Infection and skin necrosis frequently occur if it is not treated properly in the early stages. However, there is no clearly established treatment algorithm. In the acute stage, it is mainly treated with aspiration, simple compression, and incisional drainage. In the chronic stage, sclerotherapy is usually performed. If skin necrosis develops, the necrotic tissue is resected and a skin graft is needed. We describe a case of acute Morel-Lavallée lesion in the buttock region that was treated with limited incisional drainage and negative-pressure wound therapy, and also present a review of the literature.